Epidemiological aspects of bruxism at the Abidjan Odonto-Stomatological Consultation and Treatment Center. - Kamon Jean-Claude N’cho; Kouassi Ange Patrick Kouassi; Giles Thierry Maroua (Indonesian Journal of Prosthodontic, 2025)
Introduction Bruxism is a factor that both promotes and aggravates certain oral diseases. The importance of the repercussions of bruxism shows the interest of our work which is to know the frequency and the prevalence of bruxism. The general objective of our work is therefore to contribute to the epidemiological study of bruxism in Côte d'Ivoire. Method This was a descriptive cross-sectional study of three hundred (300) patients attending the Centre de Consultation et de Traitements Odonto-Stomatologiques d'Abidjan, who underwent a questionnaire and an odonto-stomatological examination. The criterion used to diagnose bruxism was that of Dr Gilles Lavigne et al. Results Our study population consisted of 300 individuals ranging in age from 4 to 82 years, the majority of whom were women [18-40 years], with a bruxism frequency of 22.33%. Our population of bruxers was predominantly female, accounting for 59.70%. Also, the prevalence of bruxism increased with age. Conclusion In our study population, our survey reveals that the prevalence of bruxism is still significant. Practitioners must therefore be provided with the appropriate equipment for better diagnosis and patient management.